Plasma and vitreous fluid levels of Dickkopf-1 in patients with diabetic retinopathy - Qiu, F (Nature Publishing Group, 2014)
PURPOSE: Dickkopf-1 (DKK-1) is a secreted inhibitor of the Wnt/β-catenin signaling pathway, which plays a pathogenic role in diabetic retinopathy (DR). We aimed to investigate whether DKK-1 levels in the plasma and the vitreous are associated with DR in type 2 diabetes mellitus (DM) patients. METHODS: Case–control study: plasma samples were collected from 125 type 2 DM including 81 DR (29 non-proliferative DR (NPDR) and 52 proliferative DR (PDR)), 44 non-DR patients (NDR), and 100 non-diabetic controls. Undiluted vitreous fluid samples were obtained from 30 PDR and 25 non-diabetic patients. DKK-1 concentrations in samples were determined using enzyme-linked immunosorbent assay. Variables were compared with the Kruskal–Wallis H test, Mann–Whitney U-test, and χ(2)-test, when appropriate. RESULTS: Plasma DKK-1 levels were significantly lower in DR patients (median: 465.77 pg/ml, range: 137.11–1190.31) than in non-diabetic controls (656.83 pg/ml, 171.63–1795.08; P<0.001) and NDR patients (693.04 pg/ml, 305.43–1218.35; P<0.001). Furthermore, DKK-1 levels were lower in PDR patients (425.21 pg/ml, 137.10–1077.32) compared with NPDR patients (594.86 pg/ml, 256.36–1393.27; P=0.003). Vitreous absolute DKK-1 levels in PDR patients (259.04 pg/ml, 104.44–596.96) were higher than in non-diabetic controls (138.26 pg/ml, 18.69–239.52; P<0.001). After normalizing by total vitreous protein concentrations, however, there was no significant difference between the groups. DKK-1 levels in vitreous were lower than those in plasma in both groups (P<0.001 for controls; P=0.002 for PDR patients). CONCLUSIONS: Decreased plasma DKK-1 levels, which may contribute to the Wnt pathway activation, are associated with the presence and progression of DR, and have potential to become a biomarker for DR.